The influence of diabatic heating in the South Pacific Convergence Zone on Rossby wave propagation and the mean flow. (15th December 2015) - van der Wiel, Karin; Matthews, Adrian J.; Joshi, Manoj M.; Stevens, David P.
Abstract : The South Pacific Convergence Zone (SPCZ) is a northwest‐southeast oriented precipitation band over the South Pacific Ocean. Latent heat release from condensation leads to substantial diabatic heating, which has potentially large impacts on local and global climate. The influence of this diabatic heating within the SPCZ is investigated using the Intermediate General Circulation Model (IGCM4). Precipitation in the SPCZ has been shown to be triggered by transient Rossby waves that originate in the Australian subtropical jet and are refracted towards the equatorial eastern Pacific. A Rossby wave triggers a SPCZ 'convective event', with associated diabatic heat release and vortex stretching. Consequently, the Rossby wave is dissipated in the SPCZ region. These features are simulated well in a control integration of IGCM4. In an experiment, convective heating is prescribed to its 'climatological' value in the SPCZ region during the Rossby wave 'events' and dynamic forcing from Rossby waves is decoupled from the usual thermodynamic response. In this experiment Rossby waves over the SPCZ region are not dissipated, confirming the vortex stretching mechanism from previous studies. Furthermore, the change in Rossby wave propagation has an impact on momentum transport. Overall, the effect of the Rossby wave‐induced convection in the SPCZ is to decrease the strength of the Pacific subtropical jet and the equatorial eastern Pacific upper‐tropospheric westerlies, by about 2–6 m s −1 . Following these changes to the basic state, two potential feedbacks in the SPCZ and larger Pacific climate system are suggested: increased SPCZ convection due to the enhancement of negative zonal stretching deformation in the SPCZ region and decreased equatorward refraction of Rossby waves into the westerly duct leading to less SPCZ 'events'. As the convective events in the SPCZ have a significant impact on Pacific mean climate, it is crucial that the SPCZ is represented correctly in climate models.